Champion of biofortification receives the World Food Prize - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
On June 28, 2016, Dr. Howarth Bouis was awarded the 2016 World Food Prize for his pioneering work developing micronutrient-rich crops through biofortification that has been a valuable contribution to ending global hunger and undernutrition. The World Food Prize is the most prominent global award for individuals whose breakthrough achievements alleviate hunger and promote global food security. This year’s award acknowledged the work of biofortification pioneers, including three scientists from the International Potato Center (CIP): Drs. Jan Low, Maria Andrade, and Robert Mwanga.